(untitled) - Cornford, Tony (London, 1996)
The book provides three interrelated categories of informations that students might find of help. Fistly, there is consideration of some theoretical and contextual perspectives. Secondly, there is a body of advice and recommandations relating to the setting up and overall management of a research project. Finally, the book offers usefull information and guidance on particular research activities to help in executing particular project tasks
Keywords: Information storage and retrieval systems